Trinomial with more than one letter

halojono91 said:
(x-2y)(3x+5y)

When x and y are multiplied together do you get XY or XY^2?

What are you supposed to do with that ? What are the instructions?
 
(x-2y)(3x+5y) =

= 3x^2 + 5xy -6xy - 10y^2
= 3x^2 -xy - 10y^2

about your question it's depens, because:

if you have: (x) (y) is equal to = xy
but if you have: (x) (xy) is equal to = x^2y
so if you have: (xy) (xy) is equal to = x^2y^2 Remember when you multiply variables you sum the exponent, that's it.

have in mind that if you have: (xy) (x+y) then is equal to: (x^2y) + (xy^2); BECAUSE WITH + VARIABLES ARE SEPARATE TERMS.

8-)

Thanks.

BY THE WAY: THIS IS SO SIMPLE THAT I DON'T YET UNDERSTAND WHY SUBHOTOSH KHAN ASKED THE INSTRUCTIONS ABOUT IT???
 
Top